Investigating the potential role of beneficial rhizobacteria for protecting grapevine health and promoting growth - Hajji-Hedfi, Lobna; Wannassi, Takwa; Tawfeeq Al-Ani, Laith Khalil; Balbool, Bassem Ayman; Tissaoui, Salma; Mougou-Hamdane, Amira; Hamdi, Wissem; Azeem, Ahmed M. Abdel; Rebouh, Nazih Y. (Frontiers in Sustainable Food Systems, 2025)
Beneficial rhizobacteria play a crucial role in promoting plant growth and enhancing soil health by producing key enzymes, facilitating nutrient cycling, and suppressing phytopathogens. This study investigated the physicochemical properties of soil from 32 grapevine sites in the Sidi Bouzid region of Tunisia and evaluated the plant growth-promoting and biocontrol potential of bacterial isolates against Botrytis cinerea, the causative agent of gray mold. Soil analysis revealed significant variation in pH (6.78 to 8.07), organic matter (0.44%−1.59%), and nutrient content, while electrical conductivity remained stable. A total of 107 bacterial isolates were isolated from soil samples and recovered, of which 97 were non-pathogenic and tested for multiple plant growth-promoting traits. Enzymatic screening revealed production of catalase, pectinase, cellulase, and chitinase among others. In vitro assays identified four isolates (H3Rh1, ZRh5, GRh5, and SRh2) with strong antifungal activity, achieving up to 99.3% growth inhibition of B. cinerea. In detached leaf assays, the isolates H3Rh1, ZRh5, GRh5, and SRh2 achieved inhibitory growth potential values of 92.33%, 93.73%, 93.02%, and 96.99% against B. cinerea, respectively. Molecular analysis confirmed the isolates as Arthrobacter globiformis, Priestia megaterium, Bacillus cabrialesii, and Bacillus mojavensis, with >99% sequence identity and deposited in GenBank. These strains also demonstrated strong plant growth-promoting attributes, including nitrogen fixation, phosphate and potassium solubilization, and indole acetic acid and siderophore production. This study highlights the biocontrol potential of native rhizobacteria as eco-friendly alternatives to chemical fungicides for managing gray mold in grapevines and promoting sustainable viticulture.